Performance of public spaces in the Kuala Lumpur metropolitan region in terms of the tropical climate - Kozlowski, Marek; Ujang, Norsidah; Maulan, Suhardi (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
The Greater Kuala Lumpur Metropolitan Region is one of the fastest growing regions in Malaysia and in the last decade has witnessed a spate of new residential, institutional and commercial development. Much of this development has been mainly market driven and guided by economic and political reasons. Such rapid property led development often neglects the local traditions, the natural settings and the local tropical climate and as a result has a detrimental impact on the surrounding public space. The aim of this study is to analyse the state of existing selected public spaces in the Kuala Lumpur Metropolitan Region against a set of recognised universal evaluative criteria for tropical design followed by identifying a set of measures to remedy existing deficiencies. The nature of this research is predominantly qualitative conducted through intense contact in the real urban life. The research methods include literature review, content analysis, field assessment and visual observations on suitable case study areas. The analysis revealed that a majority of public spaces in the region are not pedestrian friendly and do not reflect the tropical climate, being devoid of trees and vegetation. Future development of public open spaces in appreciation of the local tropical climate, local traditions, identity and character would significantly contribute to a holistic environment, viable economy and social equilibrium.